2018
DOI: 10.5455/msm.2018.30.198-203
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction and its Associated Factors After Delivery: Longitudinal Study in Iranian Women

Abstract: Introduction:Considering physical and emotional changes affecting women’s sexual function in postpartum period.Aim:This study was conducted to determine the sexual dysfunction and postpartum-related factors in Bandar Abbas women in 2016.Material and Methods:This analytical cross-sectional study used systematic random sampling on 432 postpartum women referred to Bandar Abbas Healthcare Centers. Data were collected by Demographic and Obstetrics Questionnaire and Female Sexual Function Index (FSFI) Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
20
3
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 26 publications
(34 reference statements)
4
20
3
6
Order By: Relevance
“…This may be due to postpartum vaginal and perineal rehabilitation, hormonal regulation, reduction in depression and insomnia, and adaptation to postpartum conditions. 32 Consistent with the present study, Khajehei et al 33 reported that dyspareunia is a very common complaint in the first 6 months after delivery. A US study by Pauls et al 34 also showed that women may not be able to achieve normal sexual function until 6 months postpartum.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may be due to postpartum vaginal and perineal rehabilitation, hormonal regulation, reduction in depression and insomnia, and adaptation to postpartum conditions. 32 Consistent with the present study, Khajehei et al 33 reported that dyspareunia is a very common complaint in the first 6 months after delivery. A US study by Pauls et al 34 also showed that women may not be able to achieve normal sexual function until 6 months postpartum.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the present results showed that the prevalence of dyspareunia was highest in the first 6 months postpartum as compared with other periods, and decreased with increasing postpartum duration. This may be due to postpartum vaginal and perineal rehabilitation, hormonal regulation, reduction in depression and insomnia, and adaptation to postpartum conditions 32 . Consistent with the present study, Khajehei et al 33 reported that dyspareunia is a very common complaint in the first 6 months after delivery.…”
Section: Discussionsupporting
confidence: 88%
“…Incidence data has determined that another common sexual dysfunction in women is sexual arousal disorder [33]. A study found that 40.4% of women experienced sexual arousal disorder during the postpartum period [37]. In our study, the women's level of sexual arousal before pregnancy was significantly higher than the level of sexual arousal after childbirth.…”
Section: Discussioncontrasting
confidence: 39%
“…Age and duration of marriage showed insignificant correlation to FSFI domains in contrast to Dennerstein et al [16] and Banaei et al [17] studies, respectively. This difference is because almost three quarters of the participating women were in their second decade and had been married for less than 5 years in contrast to previous studies.…”
Section: Discussionmentioning
confidence: 53%